STUDY OF FACTORS AFFECTING THE SELECTION OF A LAND TRANSPORTATION MODE OF LONG DISTANCE TRAVEL DURING A PANDEMIC (PALANGKA RAYA–BANJARMASIN ROUTE) - Ramlah, Siti; Tarita Aprilani Sitinjak; Ni Putu Diah A. Permanasuri (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2023)
The Palangka Raya route–Banjarmasin is a bustling route because it connects between provinces. On this route public transportation is bus and travel. These two modes of transportation offer costs, schedules and various supporting facilities. Added with the COVID-19 pandemi period of course the society has many considerations in choosing transportation moda that will be used. As for the purpose of this research is to know the characteristics of the demographics of users of transportation moda and factors that affect in the selection of remote travel land transportation moda during the Palangka Raya route pandemi–Banjarmasin in particular public transportation (bus and travel). In this research the data pending in the form of questionnaires that were then shared to 100 Yassoe bus respondents and travel Goddess Sumertha Sari. The questionnaires were processed using a program of SPSS 26 versions with linear reggression analysis. From analysis obtained Y=1,350+0.123X1+0.205X2+0,429X3+0.079X4. Based on the results of the reggression of four variables entirely pointing the entire variable together affects the selection of land transportation mods by the fourth contribution of the variable is 71,6% where the results of the F test are F count (59,884) > the value of F table (2,47), and the results of the four test t are count > t table (1,98525).